The Role of E-Service Quality and Price Perception: Key to Increasing Loyalty through Consumer Satisfaction - Yulihapsari, Ika Utami; Indrawan, Rully; Simarmata, Juliater; Zainal, Munawaroh (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyse the effect of E-Service Quality and Price Perception on consumer loyalty, with consumer satisfaction as a mediating variable. Methodology/Approach: In January 2024, a survey was conducted on 105 respondents based on TopBrand survey data. The sampling process used the Roscoe technique and the probability sampling method. This survey was used to test the validity and reliability of the instrument and to test the hypothesis to identify the direct and indirect effects between research variables. The study indicates that e-service quality directly affects customer satisfaction and loyalty. Results/Findings: Price perception plays an important role in shaping customer satisfaction and loyalty, where customers who consider prices fair and in line with the value, they receive are likely to feel higher Satisfaction and stronger loyalty. Satisfaction, in turn, acts as a mediator, increasing the positive impact of e-service quality and price perception on loyalty.Conclusions: E-service quality and price perception significantly influence customer satisfaction and loyalty, with satisfaction acting as a mediator in strengthening these relationships. Businesses must enhance service reliability, responsiveness, and user-friendliness while ensuring competitive and transparent pricing to improve customer retention. Implementing data-driven strategies, proactive communication, and technological innovations will further sustain long-term customer satisfaction and loyalty.Limitations: The study only focuses on the logistics sector (J&T and JNE), so the results may not apply to other industries.Contribution: Highlights the relevance of the Expectancy Disconfirmation Theory (EDT) in digital services.